As representações sociais sobre o ensinar de professores na formação continuada no ensino à distância - Antunes, Jeanne Barros (2011)
The theme focuses on social representations about teaching of teachers who are in continuing education on post graduate-lato sensu in the distance education mode of PUC-Rio aims to understand the social representations of teacher’ s t each and the possible trends of teaching practices in Rio de Janeiro St at e. The theory of social representations - TRS support s theoretically and methodologically the understanding and contribtion on thinking about the meaning of teaching and indicating possible choices of teaching practices. The social representation of teaching consists in an object where when in deep analysis and discussion allows the understanding of the operands method of the teacher, as well as proposing strategies for teacher training. For the scientific and critical need it’s amust to investigate, discuss theories that allow suchco ordination. It’s quoted the idea of teaching (MASETTO, 2000, 2003) and the proposal of UNESCO (2000). It also seeks to Pierre Levy (2000) to consider the concept of network that guides the new communication method that emerges from global interconnection. Is Searched still the idea of ways of thinking and act in gin the cyberspace and cyber culture. Thus, we see the tri angulation Pedagogy, Psychology and Technology. The investigative methodology will be qualitative (CRES WEL, 2007) with emphasis in social psychology. The data that have been processed and the analysis of the content about the continuing education of teachers regardingt heir possibilities and limitations in improving the understanding of what is wanted to be taught.